2019
DOI: 10.1017/s0007114518003859
|View full text |Cite
|
Sign up to set email alerts
|

Dairy foods and bone health throughout the lifespan: a critical appraisal of the evidence

Abstract: The consumption of high-Ca, high-protein dairy foods (i.e. milk, cheese, yogurt) is advocated for bone health across the lifespan to reduce the risk of low-trauma fractures. However, to date, the anti-fracture efficacy of dairy food consumption has not been demonstrated in randomised controlled trials but inferred from cross-sectional and prospective studies. The anti-fracture efficacy of dairy food consumption is plausible, but testing this requires a robust study design to ensure outcomes are suitably answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
(124 reference statements)
1
6
0
1
Order By: Relevance
“…Therefore, the increase in levels only in the experimental group may be due to the enriched dairy preparation. This is shown in other studies [49,50] that support these results, such as the clinical trial conducted by Manios et al In this study, 79 postmenopausal women were divided into two groups. The control group consumed their usual diet alongside an enriched dairy product, and the intervention group retained their usual diet plus a dairy product enriched with 5.7 g of vitamin D. After 8 weeks of intervention in the winter months, the treatment group had significantly increased serum vitamin levels relative to the control group [51].…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the increase in levels only in the experimental group may be due to the enriched dairy preparation. This is shown in other studies [49,50] that support these results, such as the clinical trial conducted by Manios et al In this study, 79 postmenopausal women were divided into two groups. The control group consumed their usual diet alongside an enriched dairy product, and the intervention group retained their usual diet plus a dairy product enriched with 5.7 g of vitamin D. After 8 weeks of intervention in the winter months, the treatment group had significantly increased serum vitamin levels relative to the control group [51].…”
Section: Discussionsupporting
confidence: 80%
“…Children aged between 3 and 17 years seem to take more than 50% of the recommended daily dose of calcium through dairy products as confirmed by studies carried out in France (2005–2007) and the United States ( 49 ). The latter pointed out that children aged between 2 and 18 years take about 950 mg/day through dairy products (especially milk and cheese), which represents the main source ( 55 ). The optimal quantity of phosphorus to take is in a ratio of 2:1 to calcium (in favor of the latter) since it could have the opposite effect.…”
Section: The Influence Of Macronutrients and Micronutrients On Bone Healthmentioning
confidence: 99%
“…Several randomized controlled trials in children and adults have used milk and milk products as the principal source of calcium, all showing positive effects ( 1 ). Early studies in Caucasian and Gambian children indicated that increasing milk intake may increase bone formation, and increase the levels of insulin growth factor—one (IGF-I), while supplementing with fortified milk with additional vitamin D resulted in significant increases in lumbar spine bone density compared to the controls ( 3 ). In contrast a meta-analysis as well as a review indicated that increased milk/ dairy intake may only be effective in children with a low habitual intake ( 2 ).…”
Section: Milk and Bone Health In Children And Older Adultsmentioning
confidence: 99%
“…Iuliano and Hill ( 3 ) provided a critical appraisal of the evidence for a beneficial effect of dairy foods on bone density/ bone biomarkers throughout the lifespan. Several studies have shown significant effects of regular or fortified milk on bone biomarkers reducing bone resorption, but evidence of significant effects on bone density and reduction in fracture risk are less available.…”
Section: Milk and Bone Health In Children And Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation